Low Concentrated Fractionalized Nanofibers as Suitable Fillers for Optimization of Structural-Functional Parameters of Dead Space Gel Implants after Rectal Extirpation - Bocková, Markéta; Pashchenko, Aleksei; Stuchlíková, Simona; Kalábová, Hana; Divín, Radek; Novotný, Petr; Kestlerová, Andrea; Jelen, Karel; Kubový, Petr; Firment, Peter; Fedačko, Ján; Jarošíková, Taťána; et al. (Gels (Basel, Switzerland), 2022)
Dead space after rectal resection in colorectal surgery is an area with a high risk of complications. In this study, our goal was to develop a novel 3D implant based on composite hydrogels enriched with fractionalized nanofibers. We employed, as a novel approach in abdominal surgery, the application of agarose gels functionalized with fractionalized nanofibers on pieces dozens of microns large with a well-preserved nano-substructure. This retained excellent cell accommodation and proliferation, while nanofiber structures in separated islets allowed cells a free migration throughout the gel. We found these low-concentrated fractionalized nanofibers to be a good tool for structural and biomechanical optimization of the 3D hydrogel implants. In addition, this nano-structuralized system can serve as a convenient drug delivery system for a controlled release of encapsulated bioactive substances from the nanofiber core. Thus, we present novel 3D nanofiber-based gels for controlled release, with a possibility to modify both their biomechanical properties and drug release intended for 3D lesions healing after a rectal extirpation, hysterectomy, or pelvic exenteration.
Keywords: fractionalized nanofibers; drug delivery system; gel rigidification; dead space